Outcome of Surgical Site Infection in General Surgical Practice in a District Hospital - Rahman, Ashrafur; Joty, Fahmida Sharmin (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: Surgical site infection (SSI) can affect the surgical procedures in the peripheral hospital adversely and adequate data can help in the management of this unwanted complication. Aim & Objective: The study was conducted with the aim to identify the outcome of surgical site infection (SSI) in a secondary level district hospital. Materials & Methods: A total of 192 patients, underwent general surgical procedures in the 100-bedded district hospital, Shariatpur, Bangladesh from January to December, 2016. All were observed for development of SSI for a period of 30 days after their surgical procedure. SSI cases were identified according to National Healthcare Safety Network (CDC/NHSN) guideline and Southampton wound scoring system. Univariate and multivariate analysis was done to identify significant risk factors for development of SSI. Results: Overall incidence of SSI was 20.31%. Significant risk factors for development of SSI were age, BMI, ASA grade, wound classification, diabetes, type of surgery, duration of surgery and perioperative transfusion (p<0.05). Among them, BMI (OR=1.434), diabetes (OR=8.126), type of surgery (routine/emergency) (OR=6.097), duration of surgery (OR=1.023) and perioperative transfusion (OR=2.130) were determined as independent risk factors on logistic regression. Conclusion: SSI has a relatively high incidence in rural surgical practice. Identification and control of predictable risk factors would help to reduce the incidence of SSI. J Bangladesh Coll Phys Surg 2021; 39(3): 171-177